Vegetarian diet and pregnancy outcome - Johanna Kristiina Reijonen; Kati Maaria Hannele Tihtonen; Tiina Hannele Luukkaala; Jukka Tapio Uotila (European Journal of Obstetrics & Gynecology and Reproductive Biology: X)
Objective: Vegetarian diets are becoming increasingly popular. Our aim was to evaluate the association of a vegetarian diet with pregnancy, labor, and newborn’s outcome. Study design: This retrospective case-control study included 150 women on a vegetarian diet and 300 omnivores. The data were collected from Tampere University Hospital pregnancy database from January 2015 to April 2021. Diet was a self-reported variable. Outcomes of interest were compared between the groups. The frequency of small-for-gestational age (SGA) newborns and low birth weight were primary outcomes. Other parameters concerning pregnancy, labor, and newborn served as secondary outcomes. Results: The rate of SGA at the 10 % cutoff was lower in the vegetarian group. Based on a definition of two standard deviations, SGA did not differ between the vegetarian diet group and the control group. The median birthweight was significantly higher in the vegetarian group. Gestational diabetes (GDM) was more common in the vegetarian group, however the numbers of large for gestational age (LGA) newborns were comparable between the study groups. Labor induction was more common, and the second stage of labor was longer in the vegetarian group. Preterm births (< 32+0 and < 37+0 gestational weeks) were more common in the control group. No differences were found in the mean umbilical artery pH value, 1- and 5- minutes Apgar scores or the number of newborns transferred to the neonatal intensive care unit and neonatal ward. The proportions of hypertensive disorders in pregnancy did not differ between the groups. Conclusion: According to our results, a vegetarian diet may be considered safe during pregnancy. It was not associated with an increased risk of pregnancy- or neonatal complications.